The Effect Of Workload On Fatigue In Banking Company Employees - Ratih Latiffah Khamadika; Dewi Purnamawati (Persatuan Dosen Kesehatan Masyarakat, 2026)
Bank tellers face high work demands, which put them at risk of work fatigue. This research is directed to examine the relationship between the level of workload and the condition of work fatigue in banking teller officers. The method applied is quantitative research with a cross-sectional design and the application of total sampling techniques to 32 respondents. Workload assessment is done using the NASA-TLX instrument, while work fatigue measurement is done using the IFRC questionnaire. Data processing includes descriptive analysis and analysis of intervariate relationships through the Chi-Square test. Research findings show that the largest proportion of respondents are in the very high workload category (87,5%) and a very high level of fatigue (81,3%). Statistical test results indicate a significant relationship between workload and work fatigue (p 0.05). This finding confirms that workload control is an important factor in efforts to reduce fatigue and support the improvement of employee performance.Keywords : Workload, Work Fatigue, Teller Bank